2003
DOI: 10.1093/jee/96.4.1290
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the Cry1Ac δ-Endotoxin of Bacillus thuringiensis in the Cotton Bollworm, Helicoverpa armigera (Lepidoptera: Noctuidae)

Abstract: Three laboratory strains of Helicoverpa armigera (Hübner) were established by mating of field-collected insects with an existing insecticide-susceptible laboratory strain. These strains were cultured on artificial diet containing the Cry1Ac protoxin of Bacillus thuringiensis using three different protocols. When no response to selection was detected after 7-11 generations of selection, the three strains were combined by controlled mating to preserve genetic diversity. The composite strain (BX) was selected on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
164
1
7

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(180 citation statements)
references
References 0 publications
8
164
1
7
Order By: Relevance
“…While five Cry1Ac-binding proteins were isolated from H. armigera in this study, in situ studies predicted only two binding sites (Akhurst et al, 2003;Liao et al, 1996). These in situ studies were conducted with BBMVs, which, without the membrane solubilisation step, might better reflect in vivo binding whereas the treatment of BBMVs with CHAPS as part of the affinity purification process could have exposed binding epitopes that are concealed in vivo.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…While five Cry1Ac-binding proteins were isolated from H. armigera in this study, in situ studies predicted only two binding sites (Akhurst et al, 2003;Liao et al, 1996). These in situ studies were conducted with BBMVs, which, without the membrane solubilisation step, might better reflect in vivo binding whereas the treatment of BBMVs with CHAPS as part of the affinity purification process could have exposed binding epitopes that are concealed in vivo.…”
Section: Discussionmentioning
confidence: 66%
“…All the proteins isolated in this study have predicted GPI anchor sites but only some have the mucin-like domain. These data might be reconciled by the suggestion that the two classes of binding sites identified kinetically (Liao et al, 1996;Akhurst et al, 2003) might correspond with GalNAc contained in mucin-like domains and GalNAcmodified GPI-anchors rather than two particular proteins. If this is correct then either of these features might be sufficient to enable an APN to bind Cry1Ac under the conditions reported here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research had reported resistance to Cry proteins in the Indian meal moth (Plodia interpunctella) and the diamondback moth (Plutella xylostella). Akhurst et al (2003) were able, under laboratory conditions, to select a strain of H. armigera that was resistant to the toxicity of Cry1Ac proteins, so it was clear that target pests could possibly develop resistance to the active ingredient of Ingard cotton. The cotton industry had for years grappled with the problem of chemical insecticide resistance and was reluctant to see Ingard technology wasted.…”
Section: Gm Insect Protected Cotton: An Australian Example Of Transgementioning
confidence: 99%